Educational interventions for health professionals managing chronic obstructive pulmonary disease in primary care - Amanda J Cross, - (John Wiley and Sons Ltd, 2022)
Background Chronic obstructive pulmonary disease (COPD) is a common, preventable and treatable health condition. COPD is associated with substantial burden on morbidity, mortality and healthcare resources.